Implantation of subcutaneous defibrillator is feasible and safe with monitored anesthesia care. Issue 12 (18th November 2019) - Afzal, Muhammad R.; Okabe, Toshimasa; Koppert, Tanner; Tyler, Jaret; Houmsse, Mahmoud; Augostini, Ralph S.; Hummel, John D.; Kalbfleisch, Steven J.; Iyer, Manoj H.; Flores, Antolin S.; Bhandary, Sujatha; Dimitrova, Galina; et al.
Abstract: Background: The perioperative anesthesia care during subcutaneous implantable cardioverter‐defibrillator (S‐ICD) implantation is still evolving. Objective: To assess the feasibility and safety of S‐ICD implantation with monitored anesthesia care (MAC) versus general anesthesia (GA) in a tertiary care center. Methods: This is a single‐center retrospective study of patients undergoing S‐ICD implantation between October 2012 and May 2019. Patients were categorized into MAC and GA group based on the mode of anesthesia. Procedural success without escalation to GA was the primary endpoint of the study, whereas intraprocedural hemodynamics, need of pharmacological support for hypotension and bradycardia, length of the procedure, stay in the post‐anesthesia care unit, and postoperative pain were assessed as secondary endpoints. Results: The study comprises 287 patients with MAC in 111 and GA in 176 patients. Compared to MAC, patients in GA group were younger and had a higher body mass index. All patients had successful S‐ICD implantation. Only one patient (0.9%) in the MAC group was converted to GA. Despite a similar baseline heart rate (HR) and mean arterial blood pressure (MAP) in both groups, patients with GA had significantly lower HR and MAP during the procedure and more frequently required pharmacological hemodynamic support. Length of the procedure, stay in the postanesthesia care unit, and postoperative pain was similar in both groups. Conclusion: This retrospective experience suggests that implantation of S‐ICD is feasible and safe with MAC. Use of GA is associated with more frequent administration of hemodynamic drugs during S‐ICD implantation.